Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1073/pnas.1716029115
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous tumors driven by Rb1 loss have an ongoing requirement for the RBP2 histone demethylase

Abstract: Inactivation of the retinoblastoma gene () product, pRB, is common in many human cancers. Targeting downstream effectors of pRB that are central to tumorigenesis is a promising strategy to block the growth of tumors harboring loss-of-function mutations. One such effector is retinoblastoma-binding protein 2 (RBP2, also called JARID1A or KDM5A), which encodes an H3K4 demethylase. Binding of pRB to RBP2 has been linked to the ability of pRB to promote senescence and differentiation. Importantly, genetic ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Using both genetic and pharmacological tools, we showed that inhibiting KDM5A decreases ASCL1 expression in SCLC cell lines, suggesting that KDM5A inhibition could be used as a therapeutic strategy to target ASCL1. Notably, Kdm5a is a nonessential gene in mice and Kdm5a inactivation in mice decreases Rb1 −/− neuroendocrine tumors in both prevention and treatment models (Lin et al 2011;McBrayer et al 2018). A caveat with our study is that the pharmacological inhibitor we used, KDM5-C70, is selective for KDM5 demethylases, but inhibits all four KDM5 family members at nearly equivalent IC50 values (Johansson et al 2016).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using both genetic and pharmacological tools, we showed that inhibiting KDM5A decreases ASCL1 expression in SCLC cell lines, suggesting that KDM5A inhibition could be used as a therapeutic strategy to target ASCL1. Notably, Kdm5a is a nonessential gene in mice and Kdm5a inactivation in mice decreases Rb1 −/− neuroendocrine tumors in both prevention and treatment models (Lin et al 2011;McBrayer et al 2018). A caveat with our study is that the pharmacological inhibitor we used, KDM5-C70, is selective for KDM5 demethylases, but inhibits all four KDM5 family members at nearly equivalent IC50 values (Johansson et al 2016).…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, pRB has been shown to bind and inhibit the activity of the H3K4 histone demethylase KDM5A/ RBP2/JARID1A (hereafter referred to as KDM5A), and KDM5A is required for the differentiation block induced by pRB loss (i.e., KDM5A is epistatic to pRB) in cellular models (Benevolenskaya et al 2005;Lin et al 2011). Furthermore, loss of KDM5A suppresses the growth of Rb1 −/− neuroendocrine pituitary and thyroid tumors (Lin et al 2011;McBrayer et al 2018). The role for KDM5A in neuroendocrine differentiation and SCLC tumorigenesis has been largely unexplored, although one study reported that KDM5A shRNAs slowed cellular proliferation in the SCLC cell line NCI-H446 that inherently expresses low levels of ASCL1 (Váraljai et al 2015).…”
mentioning
confidence: 99%
“…Whether this reflects different mechanisms/pathways in different cancers, or the complexity of KDM5A function in the same biological processes (as seen in the control of normal growth, discussed above), remains to be determined. In further support of a cancerpromoting role, KDM5A has been shown to be required for both the onset 108 and maintenance 109 of Rb-deficient tumors in genetically engineered mice. Perhaps not surprisingly, in some contexts KDM5A can play a disease-suppressive role, as shown in breast cancer cells treated with PI3K inhibitors 110 .…”
Section: Kdm5mentioning
confidence: 96%
“…As mentioned above, KDM5A binds to pRb to promote senescence [59]. In Rb-null tumors, KDM5A ablation prolongs survival of mice, which correlates with increased H3K4me3 [34]. While the authors did not show that KDM5A overexpression induces tumorigenesis, it is interesting to speculate that increased KDM5A activity alone may overcome senescence.…”
Section: Jumonji C Histone Demethylases Suppress Senescence Duringmentioning
confidence: 99%